Mechanical Properties of Polyolefin Fiber-Reinforced Light Weight Concrete - Arash Sedaghatdoost; Morteza Amini (Salehan Institute of Higher Education, 2017)
The utilization of polyolefin fibers in reinforced concrete can potentially enhance the properties of the concrete by changing the interfacial properties of the fiber-matrix interface. The objective of this research was to determine the mechanical properties of polyolefin fiber reinforced lightweight concrete (LWC). Compressive, flexural, and splitting tensile strengths of the sample were measured. Polyolefin fibers were added to the reinforced composite in variable amounts (0-2%). The lightweight concrete was designed to achieve compressive strength target of at least 30 MPa with a density value of 1800 kg/m3 after 28 days of storage. The results showed that the highest compressive strength was obtained in LWC containing 1% fiber led to an increase of about 8%. However, a reduction in compressive strength was observed when the amount of fiber was increased. Moreover, increasing the amount of fiber presented a growth in rupture modulus as well as splitting tensile strength.